Study of influence of blood pressure variabilities in outcome of spontaneous acute intracerebral hemorrhage in Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2024)
Background: Spontaneous intracerebral hemorrhage SICH is considered a serious disease despite progressing medical development, in which is associated with significant morbidity and mortality. Arterial hypertension is the most important risk factor for SICH and alterations in blood pressure is related to poor outcome.   Aim: The purpose of this study was to investigate the effects of blood pressure variability on the clinical course of SICH.  Materials and Methods: This was an analytical cohort prognostic study involving 107 patients with proven diagnosis of SICH at Neurology unit, Internal Medicine Department, Tishreen University Hospital, Lattakia, during the period 2022-2023.Results: Out of 107 patients,70 were male and 37 were female. Mean age of the patients was 60.33±9.7 years and hypertension represented the most frequent comorbidities(85.1%). Outcome was good in 21.5% and poor in 78.5% without presence of any significant differences between two groups regarding of age and gender(p>0.05). The following factors were detected in high frequency in patients with poor outcome: hypertension(p:0.02), diabetes mellitus(p:0.001), coronary disease(p:0.004) and smoking(p:0.0001). Means of systolic blood pressure values were significantly higher in poor outcome group on admission, during 6 hours, and 24 hours(203.1±25.4 versus 182.3±23.4,p:0.0001),( 190.5±13.4 versus171.1±15.3,p:0.0001 ), and(162.3±18.3 versus140.8±16.4,p:0.0001 ) respectively with presence of systolic pressure variability in 59 cases(55.1%). blood pressure variability was associated with the risk for hospital mortality OR: 4.8[2.1-9.8],p:0.0001and poor outcome OR:2.9[1.1-7.7],p:0.0001.      Conclusion: The current study demonstrated that presence of hypertension and the associated variability are considered modifiable warning flags that might improve final outcome of the patients with SICH